Guatemala 2007: a year of contrasts for democracy - Azpuru, Dinorah; Blanco, Ligia (Revista de Ciencia Política, 2020)
2007 was a year of contrasts for Guatemalan democracy; there were positive aspects but also serious problems. The political process in 2007 pivoted around the general elections that took place in the last quarter of the year. In the months preceding the elections violence seemed to increase, striking even members of several political parties. The high levels of insecurity in the country made this issue one of the main topics of the electoral campaign, which was characterized by negative verbal attacks between the contenders. However, both the first-round and the run-off elections were conducted peacefully and the results were promptly recognized by the parties participating in the event and validated by local and international observers. The geographic distribution of the vote was a key element in these elections given that the winning candidate, Álvaro Colom, is the first president elected without having won the capital.